Problems of interaction between philosophy and methodology of scientific knowledge in pedagogy - Bondar Volodymyr (Освітологія, 2017)
The article presents the excursion of formation and phased development the methodology of scientific knowledge as a science, in close cooperation with the scientific philosophy: its status, functions, similarities and differences in their methodological significance.